Political Campaign TKN "Fanta" Through the Movement Pemilihmuda.id in the Victory of the Prabowo - Gibran in the 2024 Presidential Election - Muhammad Rafael Fitrah Ramadhan Rochman; Restu Rahmawati (Journal of Governance and Social Policy, 2025)
This study analyzes the political campaign strategy of the National Campaign Team (TKN) “Fanta” through the movement Pemilihmuda.id in an attempt to win the Prabowo – Gibran pair in the 2024 presidential election. This movement represents a campaign innovation specifically designed to reach and optimize the potential of young voters, who will be the largest electoral group in the 2024 election. Through a hands-on approach-based approach and creative political communication, Pemilihmuda.id not only serves as a means of campaign but also as a participation space that offers direct benefits for the younger generation such as the delivery of aspirations that are directly monitored by TKN “Fanta”. This study uses descriptive qualitative methods through semi-structured interviews and secondary data to describe in depth the form of campaign strategies, communication patterns and their impact on increasing electoral support. The research findings show that community-based activities as well as emotional and participatory approaches are effective in building a positive image of Prabowo – Gibran among Generation Z. This strategy proved significant in strengthening the engagement of young voters while contributing to the couple's electoral victory